Improved Early Results for Patients with Extensively Drug Resistant Tuberculosis and HIV in South Africa - O'Donnell, Max R (2009)
SETTING: A public tuberculosis (TB) referral hospital in KwaZulu-Natal, South Africa. OBJECTIVE: To present treatment outcomes of patients with extensively drug resistant tuberculosis (XDR-TB) patients and HIV co-infection with and without HAART. METHODS: Retrospective cohort study. Eligible patients had drug susceptibility testing that met a consensus definition for XDR-TB, and agreed to treatment. Therapy was based on drug susceptibilities, available medications, and patient tolerance. RESULTS: 60 XDR-TB patients initiated therapy with a median number of 5.5 drugs. Of these 43 (72%) were HIV+, and 21 (49%) were on anti-retroviral therapy. 29 HIV infected patients (67%) had available CD4 counts; median CD4 count was 200.5 (S.D. 127.4). 31/60 patients (52%) had adverse events (AEs), and 17/60 patients (28%) had severe AEs. During follow-up, 12/60 (20%) experienced sputum culture conversion, while 25/60 (42%) patients died. None of the following was significantly associated with mortality: HIV status, previous MDR diagnosis or severe AEs. DISCUSSION: In this study it was possible to treat HIV/XDR-TB co-infected patients, and prolong survival in a resource limited setting. We highlight the challenges in treatment, including high frequencies of AEs and death. Expanded identification of cases, prompt referral for treatment, and attention to management of co-morbidities may facilitate successful treatment of in XDR-TB in HIV infected patients.